Development of algorithm and productivity calculation program of coal-pulverization systems of boilers ТП-92 - Мисак, Степан Йосифович (Technology audit and production reserves, 2014)
The urgent need to identify the actual productivity of coal-pulverization system for an extended period of operation appears in connection with the supply of coal to power plants with non-project specifications. The purpose of this article – developing an algorithm and calculation program for drying and grinding productivity of coal-pulverization system with mills 6M75U of boilers ТП-92 units of 150 MW energy unit that allows to perform calculations of actual productivity of coal-pulverization system depending on coal quality and availability of coal-pulverization system. The parameters, which measure in coal-pulverization system is impossible, to analyze the impact of some fuel characteristics of coal-pulverization system condition for drying and grinding performance and the impact of some coal-pulverization system characteristics on specific electricity consumption for coal dust preparation may be additionally determined by the developed program.